Critical Analysis of Cyberbullying Discourse - Al-Qabili, Zikra Yahya (Arts for Linguistic & Literary Studies, 2023)
The aim of this research is to examine the linguistic, rhetorical, and social practices related to cyberbullying. This involves categorizing its representations and social dimensions, understanding its methods and effects, and conducting a linguistic study of the term "bullying". To achieve these objectives, various blogs from diverse social media platforms during different time periods were analyzed using the Critical Discourse Analysis (CDA) approach, specifically the relational dialectical approach of Verkloff. The research focused on several axes, including defining the problem of bullying and its effects, tracking the term and its use in dictionaries, analyzing the Arabic linguistic code and social networking sites, examining rhetorical practices, and evaluating social practices. The findings of the study indicate that confronting bullying and its negative effects is not the sole responsibility of any one party. Instead, it is a collective responsibility shared by individuals, families, society, media, educational and governmental institutions, and private organizations, Each of these entities has an assigned role, and their roles are complementary in treating and limiting this negative phenomenon.